Crosscultural communication is means of language communication of representatives of different cultures (Herald of Journalism, 2020)
An author tells about the problems of crosscultural communication that is examined within the framework of anthropocentric paradigm in the article. Author of explains about the sources of term “crosscultural communication”, about the studied questions and objects of this theory of linguistics alluding to some scientific sources. In the article underlined an author separate types of crosscultural communication, also an author pays attention to what is going on interlanguage and crosscultural mov ing that become basis of crosscultural communication and revive the pragmatic values of lexical units. In any language exist emotionally bright, stylistic the special lexical units. These units can be pragmatic most mark brightly reflect a national calorite and signs. An author marks that such phenomena are brightly reflected in style of the spoken language.
Keywords: anthropocentric paradigm, crosscultural communication an interlanguage, language units, pragmatic value.